Emerging trends on the mechanism of pelvic organ prolapse from 1997 to 2022: visualization and bibliometric analysis - Yu, Xia; Lin, Wenyi; Zheng, Xuemei; He, Li; Yang, Zhenglin; Lin, Yonghong (Frontiers in Medicine, 2023)
Objective: At present, there is no feature description of the mechanism of pelvic organ prolapse (POP) in the literature. This study aimed to map the emerging trends regarding the mechanism of POP from inception to 2022 by bibliometric analysis and to analyze its research hotspots and frontiers. Methods: We downloaded pertinent publications from inception to 2022 from the Web of Science Core Collection (WoSCC) on 30 June 2022. The data were then examined using the Bibliometrix program in R (Version 4.1.0), CiteSpace software, the Online Analysis Platform of Literature Metrology (http://biblimetric.com), and a bibliometrix online interface. Results: A total of 290 qualified records on the mechanism of POP were identified and included in the analysis. The most productive journal was International Urogynecology Journal. Bump RC and Olsen AL were the most cited authors. Extracellular matrix, collagen, apoptosis, elastin, oxidative stress, gene expression, matrix metalloproteinase and tissue engineering were among the 25 most relevant terms. According to the analysis of trending topics, tissue engineering has become a new research hotspot. Conclusion: Extracellular matrix remodeling, oxidative stress and apoptosis are the three main directions for studying the mechanism of POP. In addition, tissue engineering has become a new research hotspot. In the future, in-depth research on the interaction between different mechanisms will be carried out, and attempts will be made to combine biomimetic materials and seed cells to achieve the regeneration and reconstruction of POP-related organs.